Synthesis of magnetite (Fe3O4)–Avastin nanocomposite as a potential drug for AMD treatment. (1st August 2018) - Zargarzadeh, Mehrzad; MadaahHosseini, Hamid Reza; Delavari, Hamid; Irajirad, Rasoul; Aghaie, Ermia
Abstract : Age‐related macular degeneration (AMD) is one of the prevailing causes of blindness in the aged over 50 years. There are several conventional treatments for AMD including laser therapy, surgery, and intravitreal injection of anti‐vascular endothelial growth factor directly into the eye. Intravitreal injection may result in various side effects such as increasing the eye pressure, eye infections, blurring vision; furthermore, it can negatively affect other body organs. In addition, large number of injections would be required to regenerate the lost vision. To overcome some of these obstacles, the work proposes a new drug delivery technique by using Avastin–Fe3 O4 nanocomposites synthesised through co‐precipitation method with approximate size of 20 nm. The saturation magnetisation ( M s ) of the synthesised iron oxide nanoparticles (NPs) was about 55.6648 emu/g which is completely suitable for movement of the (Avastin–Fe3 O4 ) NPs. Besides, the results of the flow cytometry tests showed that 90.5% of NPs were Avastin loaded. The proposed new method can be replaced with conventional treatments as the long‐term sustained release of Avastin instead of several injections as well as declining the systemic side effects due to the high concentration of Avastin in the posterior segment of the eye.